STRATEGI PENGEMBANGAN USAHA KECIL MENENGAH SEKTOR INDUSTRI PENGOLAHAN KABUPATEN BEKASI - Hari Sulistiyo; R. Aditya Kristamtomo Putra (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
The role of Micro, Small and Medium Enterprises or Small and Medium Enterprises (SMEs) in a country's economic growth is considered important. SMEs have a large and crucial contribution to the Indonesian economy. MSMEs have an important role in development and economic growth. The role of SME is not only felt in developing countries but also in developed countries. In developed and developing countries, MSME is very important, because it absorbs the most labor compared to large businesses. The contribution of MSMEs to the formation or growth of Gross Domestic Product (GDP) is greater than the contribution of large businesses. However, in reality the amount is inversely proportional to quality. Many MSME actors whose HR quality is still low, both in education and technology. The low quality of human resources has an impact on their productivity. This study aims to find out how the Development Strategy of Micro Small and Medium Enterprises in the Manufacturing Industry Sector in Bekasi District. The use of the Location Quotient (LQ) method is used to find out what business bases can be used by MSMEs based on LQ analysis calculations. The use of TOWS analysts deepens the discussion of what and how MSME strategies compete. From the LQ analysis calculation results it appears that Bekasi Regency, the processed industry business sector, is a leading sector with an LQ index number > 1. As we know, Bekasi Regency's economic strength is indeed sourced from the industrial sector. Furthermore, the SME development strategy is based on the TOWS analysis, with the characters in each of the different MSMEs. The strategies used include: SO (Strength Opportunities), ST (Strength Threat) strategy, WO (Weakness Opportunites) strategy and WT (Weakness Threat) strategy.